Students’ Confidence and Interest in Palliative and Bereavement Care: A European Study - Orkibi, Hod; Biancalani, Gianmarco; Bucuţã, Mihaela Dana; Sassu, Raluca; Wieser, Michael Alexander; Franchini, Luca; Raccichini, Melania; Azoulay, Bracha; Ciepliñski, Krzysztof Mariusz; Leitner, Alexandra; Varani, Silvia; Testoni, Ines (Frontiers in Psychology, 2021)
As part of a European Erasmus Plus project entitled Death Education for Palliative Psychology, this study assessed the ways in which Master’s Degree students in psychology and the arts therapies self-rated their confidence and interest in death education and palliative and bereavement care. In five countries (Austria, Israel, Italy, Poland, Romania), 344 students completed an online questionnaire, and 37 students were interviewed to better understand their views, interest, and confidence. The results revealed some significant differences between countries, and showed that older respondents with previous experience as formal caregivers for end-of-life clients showed greater interest in obtaining practical clinical competence in these fields. A mediation analysis indicated that students’ previous care experiences and past loss experiences were related to students’ current interest in death education and palliative and bereavement care through the mediation of their sense of confidence in this field. The qualitative findings identified five shared themes: life and death, learning about death, the psychological burden, personal experience and robust training, and four key training needs. Overall, students’ interest in studying and working with terminal illness and death are rooted in internal resources, preliminary sense of confidence, as well as external requirements.